2017
DOI: 10.3390/foods6080067
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Blown Pack Spoilage Using Anti-Microbial Packaging

Abstract: Active (anti-microbial) packaging was prepared using three different formulations; Auranta FV; Inbac-MDA and sodium octanoate at two concentrations (2.5 and 3.5 times their minimum inhibitory concentration (MIC, the lowest concentration that will inhibit the visible growth of the organisms) against Clostridium estertheticum, DSMZ 8809). Inoculated beef samples were packaged using the active packaging and monitored for 100 days storage at 2 °C for blown pack spoilage. The time to the onset of blown pack spoilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The reference strains were cultured anaerobically in pre-reduced peptone yeast extract glucose starch (PYGS) broth and stored at 4 • C until sporulation (approximately three months). Prior to inoculation all sterilized media were cooled and stored inside an anaerobic cabinet (Don Whitley Scientific Ltd., Shipley, UK), under an atmosphere of mixed gas (CO 2 and N 2 ) at 37 • C and used within 48 h. Spores were harvested using the method previously described [35]. Briefly, spore suspensions were recovered by centrifugation (7500× g, 4 • C, 10 min) and washed with saline (0.85% NaCl) (Sigma Aldrich, Arklow, Co. Wicklow, Ireland) three times.…”
Section: Bacterial Strains and Preparation Of Spore Inoculummentioning
confidence: 99%
“…The reference strains were cultured anaerobically in pre-reduced peptone yeast extract glucose starch (PYGS) broth and stored at 4 • C until sporulation (approximately three months). Prior to inoculation all sterilized media were cooled and stored inside an anaerobic cabinet (Don Whitley Scientific Ltd., Shipley, UK), under an atmosphere of mixed gas (CO 2 and N 2 ) at 37 • C and used within 48 h. Spores were harvested using the method previously described [35]. Briefly, spore suspensions were recovered by centrifugation (7500× g, 4 • C, 10 min) and washed with saline (0.85% NaCl) (Sigma Aldrich, Arklow, Co. Wicklow, Ireland) three times.…”
Section: Bacterial Strains and Preparation Of Spore Inoculummentioning
confidence: 99%
“…Sodium octanoate (SO), which is a derivative of caprylic acid, demonstrates also anti-microbial properties. Reid et al [ 181 ] incorporated it, at concentrations 2.5 and 3.5 times the MIC, into gelatin coated film and beef was packaged in it. Growth inhibition of Clostridium estertheticum , leading to significant ( p < 0.01) delay of blown pack spoilage of beef was reported.…”
Section: Natural Anti-microbialsmentioning
confidence: 99%
“…estertheticum only [51]. In an experiment to compare commercially available antimicrobials, Auranta FV (AFV; composed of bioflavonoids, citric, malic, lactic, and caprylic acids), Inbac-MDA (IMDA; composed of sodium diacetate, malic acid, mono and diglycerides of fatty acids, salt and excipients), and sodium octanoate (SO) incorporated in active packaging systems, found that AFV and SO prevented BPS within 42 days [85]. Times and temperature combinations of 240 s at 100 °C were also shown to inactivate Cl.…”
Section: Intervention and Inactivation Strategies To Reduce Blown mentioning
confidence: 99%